Cancer related information that cancer patients need - K. Osowiecka; M. Rucińska; T. Abe; A. Gwara; M. Szwiec; M. Kurowicki; A. Kieszkowska-Grudny; J. Kołb-Sielecki; A. Hagihara (Scientific Reports)
Abstract Good patient-doctor communication may help patients regulate their emotions, understand medical information, and assert their need for information and explanations. Cancer patients cited information needs as the most frequent unmet non-medical needs during oncological treatment. Adequate patient knowledge about the disease and treatment can affect the patient’s mental state, quality of life, and satisfaction with care. The study aimed to determine whether and what kind of cancer-related information is desired by cancer patients in Poland. The study was carried out on a group of 405 cancer patients using the Shortened Cassileth’s Information Styles Questionnaire (SCISQ) and Spielberg’s State-Trait Anxiety Inventory (STAI 20). Cancer patients in Poland want to receive information concerning numerous aspects of illness and treatment. Most patients wanted as much information about their disease and treatment as possible, both good and bad. Tumor localization (i.e., colorectal cancer, breast cancer), palliative intention of treatment, and low anxiety were factors increasing patients’ need for cancer information. Patients with low anxiety find it easier to express their needs and share information with others. Effective identification of information needs and non-delayed recognition and treatment of anxiety should be a part of a holistic approach to cancer care in daily clinical practice.